INSECTS - Legg, Gerald; Miles, Elizabeth; Weston, Steve; Lindsay, Ruth; Channell, Jim (Worksop : Award Publications Limited, 2022)
Packed with stunning cut-away illustrations, photos, fascinating facts and accessible text, young readers are guided on an amazing journey into the incredible world of insects by expert author, Gerald Legg. Discover the fascinating secret world of insects with expert author, Gerald Legg. With stunning photographs and cutaway illustrations, How It Works: Insects reveals how these amazing creatures hunt, eat, move, build nests, and more. From the inside of an ant nest to a close-up look at a head louse, explore the astonishing insects that live in our world's rainforests, ponds, deserts and woodlands
Includes index
For ages 7-9 years.
Keywords: Insects -- Juvenile literature; Juvenile works